Snail Shell-Clay Ceramic Composites as Sustainable Raw Materials for High-Voltage Insulators - TOBINS, Ferguson H.; ARUDI, Ishiaka S.; NURUDEEN, Abdulhakeem H. (FUDMA Journal of Engineering and Technology, 2026)
This study investigates the potential of Giant African Land Snail (GALS) shell–clay ceramic composites as raw materials for high-voltage insulators. The primary aim was to evaluate the influence of firing temperature on the physical properties of these composites and determine their suitability for electrical applications. Crushed GALS shell particles (63 μm and 75 μm) were blended with clay (
Keywords: Snail shell, ceramic composites, firing temperature, porosity, water absorption, bulk density, sustainable materials.